Comparison of gait in patients following a computer‐navigated minimally invasive anterior approach and a conventional posterolateral approach for total hip arthroplasty: A randomized controlled trial. Issue 2 (8th August 2012) - Reininga, Inge H.F.; Stevens, Martin; Wagenmakers, Robert; Boerboom, Alexander L.; Groothoff, Johan W.; Bulstra, Sjoerd K.; Zijlstra, Wiebren
Abstract Minimally invasive total hip arthroplasty (MIS THA) aims at minimizing damage to muscles and tendons to accelerate postoperative recovery. Computer navigation allows a precise prosthesis alignment without complete visualization of the bony landmarks during MIS THA. A randomized controlled trial (RCT) was conducted to determine the effectiveness of a computer‐navigated MIS anterior approach for THA compared to a conventional posterolateral THA technique on the restoration of physical functioning during recovery following surgery. Thirty‐five patients underwent computer‐navigated MIS THA via the anterior approach, and 40 patients underwent conventional THA using the conventional posterolateral approach. Gait analysis was performed preoperatively, 6 weeks, and 3 and 6 months postoperatively using a body‐fixed‐sensor based gait analysis system. Walking speed, step length, cadence, and frontal plane angular movements of the pelvis and thorax were assessed. The same data were obtained from 30 healthy subjects. No differences were found in the recovery of spatiotemporal parameters or in angular movements of the pelvis and thorax following the computer‐navigated MIS anterior approach or the conventional posterolateral approach. Although gait improved after surgery, small differences in several spatiotemporal parameters and angular movements of the trunk remained at 6 months postoperatively between both patient groups and healthy subjects. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 288–294, 2013